The Role of Hungarian Local Governments in Local Economic Development - Mezei, Cecília (Discussion Papers, 2012)
The study deals with the practice of local economic development in Hungary, and pays specific attention to the role of local governments in this process. In our interpretation local economic development means conscious intervention into the local economy. In the course of that process the actors may use internal and external resources too. The initiator of intervention may be external actors (e.g. government, European Union, foreign investment), but the key element of process is the involvement of local actors, who are the initiators of LED activities, or acceptors, or supporters, or manipulators of external development conception. We use the local economic development term in a wider sense, so the intervention into the local economy includes infrastructure development, development of public utilities, human resources development, business development, creation of internal economies, and community development too. The purpose of this article is to present a brief review of the role of some actors (e.g. central government, county governments, RDA-s, regional development councils) but first of all the role of municipal governments in economic development in Hungary. The study highlights the problems of the financing and the planning of local economic development and deals with the networking practices of local actors too. The article collects the LED tools and strategies of local governments and analyses the success of local economic development in Hungary.